Introduction to information literacy for students - Alewine, Michael C.; Canada, Mark (2017)
"Introduction to Information Literacy for Students presents a concise, practical guide to navigating information in the digital age. Features a unique step-by-step method that can be applied to any research project. Includes research insights from professionals, along with review exercises, insiders' tips and tools, search screen images utilized by students, and more. Encourages active inquiry-based learning through the inclusion of various study questions and exercises. Provides students with effective research strategies to serve them through their academic years and professional careers. Ensures accessibility and a strong instructional approach due to authorship by a librarian andaward-winning English professor." -- Provided by publisher.
Think like a detective -- Ask a compelling question -- Search for answers -- Explore possible sources -- Evaluate sources -- Create a paper trail -- Mine your sources -- Types of sources -- Reference -- Books -- Periodicals -- Statistics -- Government sources -- Webpages -- Other sources -- Now what?
Includes index.
Keywords: Gosset, William Sealy; Information literacy; Information literacy; Informationskompetenz; Studium; Wissenschaftliches Arbeiten